Diagnosis and management of neuropsychiatric symptoms in early Alzheimer's disease in the memory clinic setting: Neuropsychiatry and behavioral neurology/non‐pharmacologic interventions. (7th December 2020) - Eikelboom, Willem S.; Coesmans, Michiel; Singleton, Ellen H.; Ossenkoppele, Rik; van Swieten, John C.; van den Berg, Esther; Papma, Janne M.
Abstract: Background: Neuropsychiatric symptoms (NPS) are highly prevalent in early Alzheimer's disease (AD) and are associated with poor clinical outcomes. Although non‐pharmacological interventions are considered first‐line treatment for NPS in AD, they are rarely implemented into the memory clinic. Here, we present the protocol of our intervention study aimed to structure and standardize the detection and treatment of NPS in AD in the memory clinic, and provide preliminary data from our control group to obtain more insight in the current memory clinic care as usual (CAU) of NPS in AD. Method: We are currently enrolling a control group that receives CAU at six memory clinics in and around Rotterdam, the Netherlands. From spring 2020 onwards, a second wave of subjects will undergo the Describe, Investigate, Create, Evaluate (DICE) method in order to standardize and structure the management of NPS in AD. Primary outcomes are the quality of life of patients and their caregivers measured by the Qol‐AD. Secondary outcomes include NPS change, caregiver burden, the experiences of the participants that underwent the DICE method, and the cost‐effectiveness of the intervention. We conducted interviews with physicians to investigate the CAU for NPS in the memory clinic. Result: To date, 26 community‐dwelling patients have been enrolled in the control group together with their caregivers (n=19 AD dementia, n=7 mild cognitive impairment due to AD, mean [SD] Mini‐Mental State Examination = 23.5 [3.6]). Most common NPS presented at baseline were depression (80.8%), apathy (65.4%), and irritability (61.5%). Although we found heterogeneity in the CAU of NPS between participating sites, most memory clinics do not routinely screen for NPS (2/6 sites) and/or to carry out an elaborate assessment of NPS and its potential underlying causes (2/6 sites). Conclusion: Preliminary data on the CAU indicate a high prevalence of NPS that are currently not routinely investigated nor treated in the memory clinic. Early recognition and thorough assessment of NPS seem important first steps to facilitate the use of non‐pharmacological treatments for these symptoms in AD. Our intervention study aims to facilitate an early diagnosis and adequate management of NPS in early AD in the memory clinic.